Diversification of sales channels as a factor in the development of the life insurance market - D. A. Maksimov (Путеводитель предпринимателя, 2020)
This article discusses the main aspects of Russian life insurance market, distinguished features and prospects of the development of life insurance in the Russian Federation, provides guidance on the development of measures to stimulate the development of life insurance.